UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT PISANG KEPOK MENTAH SECARA IN VITRO - Novia Ariani; Rakhmadhan Niah (Jurnal Ilmiah Manuntung, 2019)
The incidence of infections in the gastrointestinal tract is increasing every year. Some bacteria that often cause infections in the gastrointestinal tract are Salmonella typhi, which is a bacterium that causes typhoid fever, and Shigella dysenteriae which is a bacterium that causes dysentery. Handling of infection can only be done by using antibiotics. Improper use of antibiotics can lead to resistance, so it is necessary to look for alternative treatments that come from nature to overcome resistance levels. One of them is raw Kepok banana peel (Musa paradisiaca formatypica) which has secondary metabolites such as flavonoids, alkaloids, tannins, and saponins, where these compounds have many antibacterial activities unknown to the public. This research was an experimental research. The extraction method was using the maceration method with 96% ethanol solvent. Antibacterial activity test for Salmonella typhi and Shigella dysenteriae was using diffusion method therefore the wells were divided into 7 treatment groups, namely extract concentration 0.3125%; 0.625%; 1.25%; 2.5%; 5.0%; positive control (Chloramphenicol dose 30 mg / ml for Salmonella typhi, Ciprofloxacin dose 100 mg / ml for Shigella dysenteriae), and negative control (ethanol 96%). The diameter of the inhibitory zone formed was then measured using a caliper. From the results of the research that has been done, it was found that the ethanol extract of raw Kepok banana peel (Musa paradisiaca forma typica) had inhibitory effect on the growth of Salmonella typhi and Shigella dysenteriae bacteria with the highest inhibition zone diameter of 11.36 mm and the lowest 6.45 mm for Salmonella typhi, and the highest inhibition zone for Shigella dysenteriae was 17.99 mm and the lowest was 15.13 mm. The minimum concentration of banana skin ethanol extract which had inhibitory power was 0.3125%.